2003
DOI: 10.1128/jb.185.23.6764-6772.2003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Streptococcus salivarius Lactose Permease (LacS) by HPr(His∼P) and HPr(Ser-P)(His∼P) and Effects on Growth

Abstract: The oral bacterium Streptococcus salivarius takes up lactose via a transporter called LacS that shares 95% identity with the LacS from Streptococcus thermophilus, a phylogenetically closely related organism. S. thermophilus releases galactose into the medium during growth on lactose. Expulsion of galactose is mediated via LacS and stimulated by phosphorylation of the transporter by HPr(HisϳP), a phosphocarrier of the phosphoenolpyruvate:sugar phosphotransferase transport system (PTS). Unlike S. thermophilus, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…LacS is similar to GPH permeases previously identified in lactic acid bacteria (18)(19)(20). Although LacS contains a EIIA at the carboxy terminus, it is not a PTS transporter.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…LacS is similar to GPH permeases previously identified in lactic acid bacteria (18)(19)(20). Although LacS contains a EIIA at the carboxy terminus, it is not a PTS transporter.…”
mentioning
confidence: 58%
“…Members of the LacS subfamily of GPH translocators have been described in a variety of lactic acid bacteria, including Leuconostoc lactis (26), S. thermophilus (27), S. salivarius (19), Lactobacillus delbrueckii (28), and Lactobacillus helveticus (20). LacS has been reported to have the ability to import both galactose and lactose in select organisms (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies revealed that LacS of S. thermophilus and S. salivarius becomes efficiently phosphorylated at His-552 not only by PϳHis-HPr but also by doubly phosphorylated (PϳHis,P-Ser)-HPr (134,468), which is present in large amounts in oral streptococci grown on glucose or lactose (660,893) and in lactose-grown S. thermophilus cells (134). However, in contrast to S. thermophilus, S. salivarius did not expel galactose during growth on lactose.…”
Section: Mtlmentioning
confidence: 99%
“…The export of galactose is coupled to the uptake of lactose via a counterflow mechanism. Phosphorylation of the EIIA Glc -like domain of LacS was demonstrated for S. thermophilus (60) and S. salivarius (61). It increases the affinity of LacS for its substrate and the speed of the counterflow reaction (62).…”
Section: Proteins Containing a Pts Component Fused To The N Or C Termmentioning
confidence: 99%